Optimization of the company's logistics service system (Science journal «Technical service of agriculture, forestry and transport systems», 2025)
The article explores approaches to optimizing a company's logistics service system in the context of a modern market characterized by intense competition and growing consumer demands. It is established that one of the key strategic directions in logistics development is maintaining a balance between customer service levels and logistics costs. The study analyzes existing scientific approaches to the selection of logistics strategies and substantiates the feasibility of applying the Analytic Hierarchy Process (AHP) to justify the selection of a set of logistics services aimed at achieving the company's strategic goals. The proposed methodology involves constructing a hierarchical structure comprising the overall goal, performance criteria, and key logistics service indicators serving as alternatives. Pairwise comparisons of the hierarchy elements are performed using expert evaluations, optimal indicators are identified based on the Pareto principle, and the alternatives are ranked according to their impact on the strategic objective. The practical application of the methodology is demonstrated through the case of "Sfera-Avto," a company engaged in the sale of automobiles and spare parts. The results obtained contribute to improving decision-making efficiency in logistics management and enhancing the adaptability of the logistics system to market changes. The methodology can be recommended for use by enterprises seeking to increase their logistics service level without incurring excessive cost growth.
Keywords: logistics service; logistics management; analytic hierarchy process; cost optimization; service level